Micro failure analysis of adhesively bonded joints enhanced with natural cork particles: Impact of overlap length and particles volume fraction - Alireza Akhavan-Safar; Ana Queirs Barbosa; Lucas Filipe Martins da Silva; Majid Reza Ayatollahi (Fracture and Structural Integrity)
In this work, the effects of natural particles on the micro failure mechanisms and static strength of an epoxy are studied using scanning electron microscope (SEM) technique. To this end, bulk specimens and adhesively bonded single lap joints (SLJs) containing different amount of micro cork particles were fabricated and tested. To investigate the toughening mechanisms, the fracture surfaces of the specimens were analyzed using SEM and a magnifying glass. It was shown that the deviation of the crack path and formation of micro-cracks generate multi fracture surfaces which is one of the main sources of energy absorption and resulted in higher fracture energy of the enhanced adhesives. Corks also acts as a crack stopper, stabilizes the crack propagation and prevents unstable crack growth. However, the micro analysis showed that higher contents of cork lead to agglomeration of the particles which acts as a source of stress concentration, with a higher possibility of delamination between the matrix and the micro corks. Accordingly, there is an optimum amount of cork where the best adhesive fracture toughness is reached. The results showed that the optimum value of micro particles depends on the loading conditions.